SITUS SANGIRAN : POTENSI DAN PERMASALAHAN DALAM PENGEMBANGAN DAN PEMANFAATANNYA - Muhammad Hidayat (BRIN, 2003)
The utilization of Sangiran site as a tourism and education object is very appropriate. This utilization is in accordance with the potential contained in the site and its environment, and has received support from the Regional and the Central Government. The apparent deficiencies in the utilization and development of the site are the problems of public facilities for visitors, especially the problem of public transportation from Kalijambe to the site / museum. In addition, deficiencies also occur in understanding the rules for the use of space which is a cultural heritage area, which raises problems in the preservation of the site.